A la recherche des émotions perdues - Calabi, Clotilde; Santambrogio, Marco (Rivista Italiana di Filosofia del Linguaggio, 2020)
Sometime in the past, something happened that elicited an emotional reaction in me, who took part in the event. Now I remember that event and I re-live over again the emotion I felt at the time. Our problem is, What is this re-living? We argue that when we re-live an emotion, we remember or imagine as present the event that originally triggered that emotion and we have a new emotion directed to that event